Establishing the Needs Assessment for Improving Dietary Assessment for Pakistani Population Evidence from Qualitative Study Findings - Afifa Tanweer, Mehwish Niaz, Samra Imran, Ayesha Humayun, Zaib-Un-Nisa Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Dietary assessment is one of the four major components of direct nutritional assessment. Several tools have been established for assessing the dietary intake of individuals as well as the communities. However, dietary intake is a complex exposure variable which is difficult to measure accurately. This study was conducted for needs assessment and suggestions of local dietary assessment tool users (clinical dietitians and researchers) regarding improvements in these tools. Methods: Semi structured interviews were used to conduct this study. A total of ten participants selected using purposive sampling technique were interviewed after which data saturation was reached. The analysis was performed through transcription, meaning condensation, and then establishing data driven themes and patterns. The data thus obtained was represented in tabular and narrative format. Results: Each interview took 45 minutes on average. Twenty Four Hour Recall (24HR) was the most commonly used tool of dietary assessment recorded in 13 out of 14 responses (92.8%) followed by Food Frequency Questionnaire (FFQ) recorded in 10 out of 14 responses (71.4%). A total of six themes emerged for the gaps associated with the use of dietary assessment tools as perceived by interview respondents. Conclusion: Interview data collected from local nutrition and dietetic experts regarding perceived problems in dietary assessment showed that the dietary intake data can be subject to information bias which affects the overall quality of data set. There is a need to acknowledge these errors and find out localized solutions to reduce these errors for improving data quality.